Pemanfaatan Abu Boiler Kelapa Sawit sebagai Bahan Pengisi dalam Campuran Aspal PG 70 Pada Lapis AC Mod-WC - Tetra Oktaviani; Wirdatun Nafiah Putri; Kusumadi; Nofriadi; Henny Lydiasari (LPPM Politeknik Aceh Selatan, 2024)
The Pavement Design Manual 2024, which requires the use of asphalt PG 70 for loads above 30 million ESAL and the increasing volume of palm oil waste that requires handling and reuse, as well as the need for alternative materials to be used as fillers, make it necessary to develop environmentally friendly materials by combining asphalt PG-70 and palm oil fuel ash as fillers. This pavement mixture is expected to be a mixture containing environmentally friendly road construction materials as well as a solution to the utilization of palm oil waste that can withstand high traffic loads. Testing of aggregate materials, asphalt, and asphalt mixtures was carried out at the Civil Engineering Laboratory of Medan State Polytechnic, in accordance with SNI, which refers to the General Specifications for Road and Bridge Construction Work 2018 Revision 2. The results obtained were that palm oil fuel ash as filler in asphalt mixture PG 70 gave an average value of stability above 1000 kg, density of 2-3 gr/ml, and VFA above 65% in all variations of filler content, for VIM values between 3-5% in the 50% and 75% variations, and VMA values above 15% in the 50%, 75% and 100% variations, while the flow value did not meet the standard value of 2-4 mm for all variations of filler content. Asphalt mixture PG 70 with palm oil fuel ash filler produces good density and stability values, but under repeated loading it will easily cause waves and rutting in the pavement due to the rigid nature of the mixture with a very high flow value and thus allow bleeding because the value of VFA is also very high.